Analisa Kinerja Sistem Pendingin Mesin Lokomotif Diesel Elektrik CC206 dengan Inhibitor 12l & 17l - Hidayat, Muhammad Taufik (VISA: Journal of Vision and Ideas, 2025)
Cooling water systems are important components in various industries that require temperature control or heat removal from processes or equipment. This process is important to prevent damage to equipment and to ensure operational efficiency. Therefore, research was carried out to determine the performance of the locomotive engine cooling system which occurred due to the influence of the use of 12L and 17L inhibitor fluids. The purpose of this analysis is to determine and analyze the value of the coefficient of performance. Testing was carried out on the CC206 locomotive unit using 12L and 17L inhibitor fluids. The research method was to carry out direct method calculations by taking self-load data during monthly maintenance. The results show that the greater the inhibitor fluid mixing, the better the cooling system performance by releasing heat through the radiator. The efficiency of the cooling system performance with 17L inhibitor fluid is greater than the performance efficiency of the cooling system with 12L inhibitor fluid.